Beyond counting the numbers: Shifting higher education transformation into curriculum spaces - Labby Ramrathan (Transformation in Higher Education, 2016)
Since the dawn of democracy in South Africa, the path of higher education transformation has been guided by the ‘White Paper 3: A Programme for Higher Education Transformation’. This path has largely been conceptualised within a framework of equity through redress and social justice that sought to change the face of higher education through demographic changes. Hence higher education transformation largely took on a number-counting process. The curriculum changes that have taken place thus far have largely been of an instrumental and responsive modality. In this paper I argue that deep curriculum transformation in higher education will be possible if we shift our gaze from predominantly a number-counting exercise to curriculum intellectualism. The next wave of higher education curriculum transformation would be a fundamental rethink based on emerging curriculum theories.